A városi mikroterek társadalomtörténete - Gyáni, Gábor (Tér és Társadalom, 1990)
Mainstream studies of urban space follow the traditions of the Chicago School still nowadays. Accordingly, their research topic is the residential segregation of population in large cities and related population moves. But urban space can also be studied in a different perspective: it can be examined as a scene of the most varied–individual and public–activities and can be considered in the light of values and norms related to its use. The present paper adopted the latter approach and places the counterconcepts (dichotomy) of the public and private, as well as the varied forms of social space conforming to these concepts, into the focus of analysis. From the mid-18th century onwards, the spheres of public and private have been gradually growing apart in the western countries of Europe. The present paper traces the functional transformation of the public in large cities. As a result of that process, the metropolitan public, particularly the public of streets, has become impersonal and turned into a neutral „space". The separation of the public and private is clearly visible both in the spatial structure and the building stock of large cities. This is a direct consequence of tendentious urban planning concepts patterned after Haussman's remodelling Paris in the second half of the 19th century. The metropolis thus reborn, through the inventions of boulevards and theoroughfares, having a symbolic value, could serve both the practical needs of use by ever growing masses of people, the functions of traffic, and a new kind of need for the impersonal outdoor public. At the same time, public and semi-public spaces were mushrooming all over to serve the needs of strangers, the individuals of the metropolitan masses, for being in public. The dichotomy of public and private has evolved even within the private sphere: the family and the home. There is a distinct division in the spacious dwellings of the middle- and uppermiddle- class between living-spaces of family members and domestic aids; and an isolated use of space by sex and age within the family has also soon become general. Finally: some „family rooms", primarily the bedroom, served strictly and specifically the needs of privacy, while others, like the parlour, were explicitely reserved for social life. Bringing about and controlling the impersonal and neutral character of the street has also become an official task. The official-police supervision of population has become particularly pressing in the living districts of lower social strata in order to make their residents respect the bourgeois code of behaviour in public. All this indicates, at least indirectly, that social orientation within cities reaching giant proportions, where urban community is becoming a mass society, is getting more and more a matter of orientation by spatial location. In the world of strangers, the knowledge required by everyday living cannot solely rely on the routine of a trained eye, the „reading" of the urban "texture" depends on the urbanites' awareness of where is what and who. One of the direct causes arousing increased official control was a different, from the bourgeois norms, notion attributed to the use of space by certain social groups and subcultures and their limits of behaviour in public being placed somewhere else. This is emphasized by the fut that ina modern metropolis, partly as a result of tendentious urban planning interventions, social groups are more segregated than earlier. Segregation was used, among others, for prevention from revolving epidemics (cholera) which, due to their spatial vicinity, also afflicted the upper classes. The (inner) city and the workers' peripheral residential distritcs were therefore also significantly dissimilar as symbolic spaces. The city had sacral and ceremonial functions while peripheries could not gain such an acceptation, for the very reason that the informal looseness or indecency of street-life there has been for long preserved, in spite of official fights against it. The institutionalization of municipal police in most European cities in the middle of last century was largely derived from the requirement of a close and constant control over public places in these districts. Police supervision of the time, saturated with the ethos of bourgeois moral standards, was called to neutralize and impersonalize the public in these parts of the city. The „efficiency" of police work was strongly dependent on the extent to which the urban „texture" was intelligible ina policeman's eyes; on how much a supervisor of the public sphere could be trained to become familiar, also visually, with the city. Besides, there were, of cciurse, municipal regulations in large number intended to enforce the norms of bourgeois behaviour. These regulations and the policemen, who act for their implementation, confine the life functions, which are visible for the widest public, to an ever smaller circle and thereby compel community members to sequester themselves, for enjoying public life, in newly mushrooming specific micro spaces, public or semi-public places, specialized to fulfil one single function.